2017
DOI: 10.1016/j.ijpddr.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoproteins play a role in ivermectin resistance in cyathostomins

Abstract: Anthelmintic resistance is a global problem that threatens sustainable control of the equine gastrointestinal cyathostomins (Phylum Nematoda; Superfamily Strongyloidea). Of the three novel anthelmintic classes that have reached the veterinary market in the last decade, none are currently licenced in horses, hence current control regimens focus on prolonging the useful lifespan of licenced anthelmintics. This approach would be facilitated by knowledge of the resistance mechanisms to the most widely used anthelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 81 publications
1
25
0
Order By: Relevance
“…The different effects of IVM on P-gp expression in mouse hepatocytes, intestinal cells, and human cancer cells may be due to the difference of tissues, animal species, and the drug doses used. Also, there were several reports showing that the anti-parasitic drug IVM was the P-gp substrate, and P-gp played a role in the IVM resistance in parasites and altered function of P-gp in blood-brain barrier would result in severe IVM-induced neurotoxicity [4446]. In our study, we indeed found that IVM inhibited P-gp function (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The different effects of IVM on P-gp expression in mouse hepatocytes, intestinal cells, and human cancer cells may be due to the difference of tissues, animal species, and the drug doses used. Also, there were several reports showing that the anti-parasitic drug IVM was the P-gp substrate, and P-gp played a role in the IVM resistance in parasites and altered function of P-gp in blood-brain barrier would result in severe IVM-induced neurotoxicity [4446]. In our study, we indeed found that IVM inhibited P-gp function (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to CYPs and UGTs, the effect of ABZ and ABZSO on expression of efflux transporters P-glycoproteins (P-gps) was also studied as P-gps have been implicated in the multidrug resistance of different parasitic nematodes in livestock [14]. Although the increased transcription of P-gps has been mainly associated with resistance to IVM and other macrocyclic lactones [37,38], the participation of P-gps in ABZ resistance cannot be excluded. In our study, exposure to ABZ and ABZSO affected transcription levels of six (out of eight tested) transporter genes in H. contortus adults.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp, encoded by the Abcb1 gene, belongs to the family of adenosine triphosphate (ATP)-binding cassette transporters and is usually localized in excretory and barrier-function tissues, such as the kidney and intestine [6,7]. P-gp can utilize the hydrolysis of ATP to energize the efflux of a broad range of substrates, including commonly used antimicrobial agents licensed in veterinary medicine (e.g., ivermectin, enrofloxacin, and danofloxacin) [8,9,10], influencing the absorption, distribution, and excretion of substrates [11]. Therefore, overcoming P-gp efflux is a strategy to improve the absorption and pharmacokinetics of substrates.…”
Section: Introductionmentioning
confidence: 99%